Measuring the Financial Resilience of Indonesian Banking Sector under Geopolitical Uncertainty Using Panel Vector Autoregression (PVAR) - Nisak, Khoirun; Setyowati, Endah; Najib, M. Thoha Ainun (The International Journal of Financial Systems, 2025)
Geopolitical tensions can affect the stability of companies, including Indonesia's banking sector. Geopolitical risk, as measured by the Geopolitical Risk Index (GRI), is an external factor that reflects economic and political uncertainty arising from global adverse events. This study aims to understand the dynamics of the interaction of geopolitical risk on the stability of banking indicators, including ROA, ROE, CAR, and NPL. Furthermore, this study aims to assess financial resilience in the banking sector amid geopolitical tensions. Sampling was conducted across banking categories, including KBMI 4, KBMI 3, Islamic banks, and regional development banks. The data used are quarterly panel time series from 2015 to 2024. The analysis was conducted using Panel Vector Autoregression (PVAR) with the Generalised Method of Moments (GMM) approach. The results show that the impact of the GRI shock on banking indicators is short to medium-term, with the most significant effects on profitability (ROA, ROE) and credit quality (NPL). The results confirm that global geopolitical pressures play a dominant role in explaining fluctuations in bank indicators in Indonesia, particularly capital efficiency and capital structure. Based on the dynamics of these interactions, Bank A, Bank B, Bank D, and Bank E are classified as more resilient, and Bank C, Bank F, Bank G, and Bank H are classified as less resilient. More resilient banks are characterised by a low GRI impact on ROA and CAR, and a quick return to stability, while less resilient banks have a high GRI impact on ROE and CAR.